Efektifitas Metode Hypnoteaching untuk Meningkatkan Kemampuan Belajar Berhitung pada Anak Kelompok B di TK An-Nur Perumahan Griya Srimulya Palembang - Erni Muliddya; Taty Fauzi; Rahmah Novianti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study was to determine the effectiveness of the implementation of the Hypnoteaching in Improving the Learning Ability to count in Group B Children in An-Nur Kindergarten, Griya Srimulya Housing, Palembang. This research was conducted in An-Nur Kindergarten, Griya Mulya Housing, Palembang City. The time of the research was carried out in the academic year 2021-2022, starting from March-April-May 2022. The study took the type of cluster sampling, the research sample was divided into 2 classes, the experimental class, and the control class. the number of samples in this study was 15 students in class B2 in the experimental class and in-class B1 as many as 15 students in the control class. In this study, the t-count results were 2.898 where the t-table value was 2.131 at a significance level of 0.05 and with a one-sided test. Because the t-value obtained is greater than the t-table value of 2.898 > 2.131, the null hypothesis (Ho) is rejected and the alternative (Ha) is accepted. This means that there is effectiveness in increasing early childhood numeracy skills by using the hypnoteaching in An-Nur Kindergarten, Griya Srimulya Housing, Palembang.